A CROSS-SECTIONAL PROSPECTIVE STUDY ON ANTIMICROBIAL RESISTANCE PROFILES OF COMMON BACTERIAL PATHOGENS CAUSING URINARY TRACT INFECTIONS AMONG PATIENTS AT MENGO HOSPITAL, KAMPALA DISTRICT. - Aramalo , Saviour Yoacel; Akullo , Mirriam; Oromcan , Benjamin Wathum (Student's Journal of Health Research Africa, 2025)
Introduction Urinary Tract Infection (UTI) is a common disease affecting all age groups and is increasingly difficult to treat due to antimicrobial resistance. Methods This study assessed the prevalence of UTIs and antimicrobial resistance profiles in patients at Mengo Hospital, Kampala. A cross-sectional, prospective study was conducted from March to May 2023. Mid-stream urine samples were analyzed using macroscopic, microscopic, Gram staining, culture, biochemical tests, and antibiotic sensitivity testing. Data was processed and analyzed using SPSS version 25. Results The results showed that 70.4% of patients had UTI, with a higher occurrence in females (72.7%) than in males (27.3%). UTI prevalence peaked at 30-39 years (37.5%). Common pathogens were Escherichia coli (20.8%), Staphylococcus aureus (15.2%), and Candida albicans (12%). Antimicrobial resistance was highest against Clindamycin (92%), Erythromycin (89%), and Ciprofloxacin (80%). Imipenem (96%), Meropenem (85%), and Vancomycin (78%) showed better sensitivity. Conclusions UTIs and antimicrobial resistance are significant public health concerns at Mengo Hospital. Women and individuals aged 30-39 years are at higher risk. Resistance varies widely, emphasizing the need for targeted antibiotic use. Recommendations The current study recommends routine UTI screening for high-risk patients. Antibiotic sensitivity testing should be done before treatment. Empiric therapy should be emphasized with effective antibiotics like Imipenem, Vancomycin, and Meropenem, considering local resistance patterns. Public awareness campaigns on UTI prevention and responsible antibiotic use should be carried out. Further research should be done on UTI epidemiology and resistance patterns to inform healthcare policies.